PENGARUH KOMPOSISI DAN DOSIS MEDIA TERHADAP PERTUMBUHAN CACING SUTRA (Tubifex sp.) - Hafsah, Hafsah; Lumbessy, Salnida Yuniati; Lestari, Dewi Putri (Journal of Fish Nutrition, 2023)
This study aims to analyze the effect of media composition and dose on the growth of silkworms. The test animals used in this study were silkworms (Tubifex sp.). The method used in this study was an experimental method using a completely randomized design (CRD) consisting of 5 treatments and 3 replications in order to obtain 15 experimental units, namely P1 (50% fermented chicken manure, 25% fermented tofu dregs and 25% tapioca meal), P2 (50% sludge, 25% fermented tofu dregs and 25% tapioca meal), P3 (50% fermented chicken manure, 25% fermented tofu dregs and 25% fermented bran), P4 (50% mud, 25% tofu dregs fermented and 25% Fermented Bran), P5 (25% fermented chicken manure, 25% mud, 25% fermented tofu dregs, 25% Fermented Bran). The results showed that there was no effect between treatments on absolute growth and productivity but the use of substrates in silkworm cultivation for 30 days with a composition of 25% fermented chicken manure, 25% mud, 25% fermented tofu dregs and 25% fermented bran could increase absolute growth. silk worms amounted to 7.2 g and a productivity value of 0.76 g / cm2.